Selective uptake and sensing of nitrate in poly(3, 4-ethylenedioxythiophene). Issue 1 (December 2017) - Rudd, Sam; Dalton, Michael; Buss, Peter; Treijs, Amanda; Portmann, Michael; Ktoris, Nick; Evans, Drew
Abstract Nitrogen (N) as a nutrient, in the form of nitrate (NO3 − ), is essential for plant growth. Chemical fertilizers are used to increase crop yields, but overuse can lead to forms of environmental pollution necessitating methods to detect and monitor the level of NO3 − in-situ in agricultural soils. Herein we report for the first time the NO3 − selectivity of the inherently conducting polymer poly (3, 4-ethylenedioxythiophene) (PEDOT). This selectivity occurs when PEDOT thin films are exposed to an aqueous environment containing not only NO3 −, but a mixture of other ions present in concentrations (ppm) typical of real agricultural soil. The PEDOT sensitivity to absorb NO3 − from solution is determined to be <1 ppm.